Analisis Uji Performa Aplikasi Dari Hasil Implementasi Refactoring Arsitektur Monolitik Ke Mikroservis dengan Decomposition dan Strangler Pattern - Riyanto; Irman Hermadi; Yani Nurhadryani (APIC, 2023)
The SmartCampus application is still built with a monolithic architecture, where all components are tightly integrated into one unit. The increasing complexity of user scalability and service demands within the information system with a monolithic architecture is evident in the application's declining performance. In this research, a performance analysis is conducted by implementing refactoring from a monolithic architecture to microservices using the decomposition and strangler patterns. The Decomposition pattern divides the monolithic application into several business domains based on their main service categories, while the strangler pattern breaks down the business domains into microservices by replacing specific functions with new services through the stages of transform, co-exist, and eliminate. Once the new functionalities are ready, the old components are deactivated, and the new services are put into operation. The application's feasibility and quality considerations are assessed using the ISO/IEC 25010 model, which comprises eight characteristics: functionality suitability, performance efficiency, compatibility, usability, reliability, security, maintainability, and portability. The performance of the resulting microservices application is tested using different performance testing types, such as load testing, spike testing, stress testing, and soak testing. Microservices showing satisfactory performance improvements will be isolated using container technology to optimize application resource efficiency and anticipate long-term needs